Geopolitics of Finance: The Impact of Global Economic Fragmentation on Multinational Corporate Risk Management Strategies - Arulfalah Nurwahid (Journal of Management Economic and Financial, 2025)
The fragmentation of the global economy triggered by geopolitical tensions, such as trade wars, financial sanctions, and supply chain disruptions, further pressured the financial stability of multinational corporations. This phenomenon emphasizes the importance of studying the geopolitics of finance, which is the close relationship between geopolitical dynamics and international financial architecture. This study aims to analyze the impact of global fragmentation on the financial architecture of multinational corporations, evaluate the risk management strategies adopted, and formulate its systemic implications. The research method used a mixed methods approach, with secondary data sourced from the IMF, World Bank, UNCTAD, as well as geopolitical risk indexes, and primary data through semi-structured interviews with corporate financial risk managers. Qualitative analysis was carried out by thematic content analysis, while quantitative analysis used data panel regression to measure the influence of macro variables on the company's financial stability. The results show that the decline in global trade and FDI flows increases the financial risk of companies, while the rise in the geopolitical risk index is negatively correlated with corporate stability. Multinational companies respond to this condition with a strategy of geographical diversification, the use of derivative instruments, and financial regionalization. However, the strategy also poses systemic implications in the form of hidden risks (hidden leverage) and increased regional financial concentration. These findings confirm that corporate risk management cannot be separated from geopolitical analysis, and demand international policy coordination to prevent deeper fragmentation of the global financial system.